Cellulitis with Decreased Consciousness - Alma Soviana Soefian (Universitas Muhammadiyah Manado, 2025)
Cellulitis is a bacterial skin and subcutaneous infection caused by the disruption of the skin barrier, immune dysfunction, and/or circulation disorders. It has various risk factors, one of which is uncontrolled diabetes mellitus. Hygiene is also crucial for prevention and long-term management to prevent reinfection. A 52-year-old male presented with decreased consciousness 2 days prior admission. He also had bulla, edema, and pain in his right lower limbs. He had a history of uncontrolled diabetes mellitus. He appeared severely ill with a Glasgow Coma Scale (GCS) of 8 (E2M4V2), hypotension, and tachycardia. At 1/3 distal right cruris and right dorsum of the foot, there were erythematous and ill-defined red-to-purplish black hyperpigmentation with multiple plaque-sized bullae with irregular margins and warmth on palpation. The laboratory examination demonstrated hyperglycemia (733 mg/dL). He was treated in the Intensive Care Unit (ICU) with multidisciplinary therapy. Cellulitis is a significant health burden because it is associated with increased hospitalization rates and medical costs. If prompt treatment is not given, it can lead to severe infection or sepsis. A holistic therapy is required, including controlling the predisposing factors, maintaining hygiene, symptomatic therapies, and antibiotics to prevent reinfection and improve the outcomes of cellulitis. Risk factor control and hygiene maintenance are crucial since they are effective preventive measures and long-term management of cellulitis, leading to patients’ improved health conditions and quality of life, also lowering the incidence of cellulitis and health burdens.